Requirements of mHealth-Based Medication Management Systems (International Journal of Innovative Research in Computer Science & Technology, 2018)
Medication error is one of the healthcare  challenges which effects 10 percent of individuals  around the world and medication management is a  complicated process including multiple activities. One  of these activities is medication intake which is handled  by patients. Technologies, specifically mobile health  technologies are potential solutions for medication error  and medication nonadherence. Moreover, designers  need to be familiar with system requirements which are  inducted from user’s goals. Therefore the interaction  design method is an appropriate method to design the  medication management systems. According to the  importance of medication management, the researches  performed a review study about mHealth-based  medication management systems in order to extract the  system requirements and usable technologies in this  area to help the designers to design efficient system.
Keywords: Medication Adherence; Medication Management; Mobile Application; Mobile Health